The Parenchyma of Secondary Xylem and Its Critical Role in Tree Defense against Fungal Decay in Relation to the CODIT Model - Morris, Hugh; Brodersen, Craig; Schwarze, Francis W. M. R.; Jansen, Steven (Frontiers in Plant Science, 2016)
This review examines the roles that radial and axial parenchyma (RAP) plays against fungal pathogens in the secondary xylem of wood within the context of the CODIT model (Compartmentalization of Decay in Trees), a defense concept first conceived in the early 1970s by Alex Shigo. This model, simplistic in its design, shows how a large woody perennial is highly compartmented. Anatomical divisions in place at the time of infection or damage, (physical defense) alongside the ‘active’ response by the RAP during and after wounding work together in forming boundaries that function to restrict air or decay spread. The living parenchyma cells play a critical role in all of the four walls (differing anatomical constructs) that the model comprises. To understand how living cells in each of the walls of CODIT cooperate, we must have a clear vision of their complex interconnectivity from a three-dimensional perspective, along with knowledge of the huge variation in ray parenchyma (RP) and axial parenchyma (AP) abundance and patterns. Crucial patterns for defense encompass the symplastic continuum between both RP and AP and the dead tissues, with the latter including the vessel elements, libriform fibers, and imperforate tracheary elements (i.e., vasicentric and vascular tracheids). Also, the heartwood, a chemically altered antimicrobial non-living substance that forms the core of many trees, provides an integral part of the defense system. In the heartwood, dead RAP can play an important role in defense, depending on the genetic constitution of the species. Considering the array of functions that RAP are associated with, from capacitance, through to storage, and long-distance water transport, deciding how their role in defense fits into this suite of functions is a challenge for plant scientists, and likely depends on a range of factors. Here, we explore the important role of RAP in defense against fungal pathogens and the trade-offs involved from a viewpoint for structure-function relations, while also examining how fungi can breach the defense system using an array of enzymes in conjunction with the physically intrusive hyphae.